META-INSTI: metabolic adverse events following integrase strand transfer inhibitor administration in spontaneous adverse event reports - Milena M Murray; Lara Fakhouri; Spencer E Harpe (BioExcel Publishing Ltd, 2023)
Background: Metabolic effects of integrase strand transfer inhibitors (INSTIs) have been reported. The FDA Adverse Event Reporting System (FAERS) is a publicly available database that captures spontaneously reported adverse events. The objective of this study was to evaluate the relationship between INSTIs and metabolic adverse events using the FAERS database. Methods: FAERS data were queried from quarter 4 of 2007 through quarter 4 of 2019 and limited to adults. The Standardized MedDRA Query for 'hyperglycaemia/new-onset diabetes mellitus' (H/DM) was used to identify metabolic adverse events of interest. Weight gain was analysed as a separate event. Reporting odds ratios (RORs) and 95% CIs were calculated for the INSTI class and individual agents. Results: Over 10.1 million FAERS reports were identified. Any INSTI was mentioned as a primary and/or secondary suspect agent in 18,400 (0.18%) reports (bictegravir: 1414 [0.01%]; dolutegravir: 7840 [0.08%]; elvitegravir: 4034 [0.04%]; raltegravir: 5551 [0.05%]). RORs (95% CI) for H/DM and weight gain for any INSTI were 1.20 (1.15-1.27) and 2.16 (1.96-2.38). For individual agents, RORs (95% CI) for H/DM and weight gain were as follows: bictegravir, 1.23 (1.10-1.37) and 6.82 (5.50-8.41); dolutegravir, 1.28 (1.19-1.39) and 1.86 (1.58-2.18); elvitegravir, 0.76 (0.56-1.02) and 1.63 (1.37-1.92); and raltegravir, 1.00 (0.90-1.11) and 3.29 (2.77- 3.91). H/DM was noted in 159 bictegravir and 712 dolutegravir reports. Conclusion: Overall, H/DM was associated with bictegravir and dolutegravir and weight gain with all INSTIs. Clinicians should know the potential relationship between INSTIs and metabolic effects and institute appropriate monitoring.